2010
DOI: 10.3174/ajnr.a2192
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Radiation Dose in Patients Admitted with Subarachnoid Hemorrhage: A Prospective Study Using a Self-Developing Film Badge

Abstract: BACKGROUND AND PURPOSE:While considerable attention has been directed to reducing the x-ray dose of individual imaging studies, there is little information available on the cumulative dose during imaging-intensive hospitalizations. We used a radiation-sensitive badge on 12 patients admitted with SAH to determine if this approach was feasible and to measure the extent of their x-ray exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…We reported cumulative skin doses, obtained from the cumulative air kerma at the patient entrance reference point and displayed by most of the modern x-ray systems, 13 while other authors have measured or estimated peak skin doses. [7][8][9][10][11][12][13] Table 2 (adapted by the authors) compares the results reported by several authors. Our cumulative skin doses and DAPs are in the range of other published values.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We reported cumulative skin doses, obtained from the cumulative air kerma at the patient entrance reference point and displayed by most of the modern x-ray systems, 13 while other authors have measured or estimated peak skin doses. [7][8][9][10][11][12][13] Table 2 (adapted by the authors) compares the results reported by several authors. Our cumulative skin doses and DAPs are in the range of other published values.…”
Section: Resultsmentioning
confidence: 85%
“…6 Several evaluations of cumulative skin dose have been made in interventional neuroradiology procedures. [7][8][9][10][11][12][13] Radiation-induced skin injuries can sometimes occur after a clinically complex procedure, but may also, on other occasions, result from the use of inappropriate equipment or poor operational techniques. The ICRP states that acute radiation doses may cause erythema at 2 Gy and delayed skin necrosis at 12 Gy.…”
mentioning
confidence: 99%
“…We did not directly measure patient doses by using a dosimeter on each patient's head, as was undertaken for example by Mamourian et al [7] in their prospective study. In our retrospective study, however, we included a larger number of patients, and took advantage of the very detailed individual PACS/RIS patient dose records and used anthropomorphic phantoms to mimic real CT and coiling procedures for estimation of organ equivalent doses in inner organs as well.…”
Section: Limitations Of This Studymentioning
confidence: 99%
“…Mamourian et al [7] measured the cumulated skin dose in 12 patients admitted with SAH using a self-developing film badge placed behind the right ear. They found good correlation between the measured dose and the number of CT examinations and length of stay in the ICU.…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation